2018
DOI: 10.1017/s0714980818000193
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Patients in Rehabilitation with Hip Fracture: A Retrospective Chart Review

Abstract: Hip fracture rehabilitation has two streams: high tolerance short duration (HTSD) and low tolerance long duration (LTLD). This study examined patient characteristics and outcomes in HTSD and LTLD associated with length of stay (LOS) and discharge destination. We retrospectively examined patients' medical charts following hip fracture surgery and collected demographic, functional, and health characteristics. A statistical analysis was done to describe the differences between HTSD (n = 73) and LTLD (n = 57) pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
1
2
0
2
Order By: Relevance
“…The median age of participants in our study is consistent with data from a systematic review of randomized controlled trials of inpatient geriatric rehabilitation, which reported mean ages of participants in the included studies ranging from 74.2 to 86.0 2 . In addition, the final cohort of 251 patients over a 1-yr period constitutes one of the larger chart reviews of geriatric rehabilitation populations, which have abstracted data from between 116 and 215 charts 3,4,33,35 . As with most chart abstraction, the data relied on accurate documentation by nurses, physicians, and allied health members, which may be subject to human error and lead to exposure misclassification of certain variables.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The median age of participants in our study is consistent with data from a systematic review of randomized controlled trials of inpatient geriatric rehabilitation, which reported mean ages of participants in the included studies ranging from 74.2 to 86.0 2 . In addition, the final cohort of 251 patients over a 1-yr period constitutes one of the larger chart reviews of geriatric rehabilitation populations, which have abstracted data from between 116 and 215 charts 3,4,33,35 . As with most chart abstraction, the data relied on accurate documentation by nurses, physicians, and allied health members, which may be subject to human error and lead to exposure misclassification of certain variables.…”
Section: Discussionsupporting
confidence: 77%
“…2 In addition, the final cohort of 251 patients over a 1-yr period constitutes one of the larger chart reviews of geriatric rehabilitation populations, which have abstracted data from between 116 and 215 charts. 3,4,33,35 As with most chart abstraction, the data relied on accurate documentation by nurses, physicians, and allied health members, which may be subject to human error and lead to exposure misclassification of certain variables. Furthermore, although we did not find that living alone predicted adverse discharge, it is possible that our sample had other support networks such as community or family members not captured in our data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Több cikk említi tényezőként a betegnek a sérülés előtti lakóhelyét is. Ezek elsősorban a saját otthonukban és a szociális ellátóintézményekben lakó betegek csoportjait különböztetik meg [24,29,30], de említésre kerül a városi és a vidéki ellátás különbsége is [24,30]. A dementia több közlemény szerint hátrányosan befolyásolja a rehabilitációra kerülést [23][24][25], hiszen hatással van az együttműködési képességre, bár a gyógytorna a demens betegekre is kedvezően hat [31].…”
Section: Eredeti Közleményunclassified
“…A beteg együttműködési képességét befolyásoló társbetegségek (dementia, mentális betegségek, alkoholbetegség) esetében szignifikánsan kisebb esélye van az intézményi rehabilitációs ellátásnak. Ezen megállapításaink összhangban vannak a szakirodalommal [23][24][25][26][27][28][29][30][31][32], és a betegállapot-jellemzők eredményei tükrözik a szakmai ajánlásokban megfogalmazott követelményeket [21,22].…”
Section: Megbeszélésunclassified